Hemolytic Uremic Syndrome Caused by Enteroviral Infection - Ming-Dar Lee; Chin-Yuan Tzen; Chun-Chen Lin; Fu-Yuan Huang; Hsi-Che Liu; Jeng-Daw Tsai (Pediatrics and Neonatology)
A 4-year-old boy presented with enteroviral infection complicated with atypical hemolytic uremic syndrome (aHUS). Enterovirus RNA was detected by reverse transcription polymerase chain reaction (RT-PCR) of both blood and kidney biopsy specimens. A survey of the complement system did not reveal a specific complement defect. Supportive therapy with blood components transfusion, plasma therapy, and immunosuppressants was administered, however, renal function did not recover. The results of this report demonstrate that the enterovirus is the cause of aHUS.